Resilient Financial Systems Can Soften the Next Global Financial Crisis. Issue 6 (1st November 2020) - Hynes, William; Trump, Benjamin D.; Love, Patrick; Kirman, Alan; Galaitsi, Stephanie E.; Ramos, Gabriela; Linkov, Igor
Abstract: Is there a way to soften the impact of another financial crisis? As national governments and global institutions grapple with the coronavirus pandemic, popular discussion has turned to how countries might overcome the social, economic, and financial disruption posed by the virus and its multi-system fallout. One lesson learned from the Global Financial Crisis of 2008 is that a drive for efficiency and the elimination of redundancy characterized the global financial system of the mid-2000s, and left much of the world exposed to systemic disruption. An overemphasis upon protecting or hardening core systems of governance and finance may not adequately protect against a range of disruptions in an uncertain future. Instead, resilience-thinking is needed to better position national and global financial institutions towards a recovery-oriented path. We describe how resilience-based policy can help lessen the long-term impacts of financial disruption posed by unpredictable events such as a pandemic.